Hysteretic Behavior of Eccentrically Loaded Reinforced Air-Entrained Concrete Columns under Combined Effects of Freeze-Thaw Cycles and Seawater Corrosion - Jieqiong Wu; Jian Zhang; Bo Diao; Shaohong Cheng; Yinghua Ye (Advances in Civil Engineering)
Besides service loads, reinforced concrete structures in cold coastal seismic regions are subjected to multiple attacks of freeze-thaw cycles and seawater corrosion as well as the earthquake struck. An experimental study was conducted to investigate the seismic response of eccentrically loaded reinforced air-entrained concrete columns under alternative actions of freeze-thaw cycles and chloride corrosion. Results show that, after 300 times of freeze-thaw cycles alternated with 100 times of seawater immersion, the hysteretic behavior of the eccentrically loaded columns manifested an apparent asymmetric pattern. Under forward cyclic load, the existence of larger eccentric load rendered the reduction of the ultimate load and the ductility of a column by up to 20.3% and 46.05%, respectively, but it had a positive effect if reverse cyclic load was applied. The presence of eccentric load could have a considerable impact on the seismic behavior of reinforced air-entrained concrete columns served in an aggressive environment.